Assessing Insecticide Susceptibility of Laboratory Lutzomyia longipalpis and Phlebotomus papatasi Sand Flies (Diptera: Psychodidae: Phlebotominae) - Denlinger, David S. (J Med Entomol, 2015)
Chemical insecticides are effective for controlling Lutzomyia and Phlebotomus sand fly (Diptera: Psychodidae) vectors of Leishmania parasites. However, repeated use of certain insecticides has led to tolerance and resistance. The objective of this study was to determine lethal concentrations (LCs) and lethal exposure times (LTs) to assess levels of susceptibility of laboratory Lutzomyia longipalpis (Lutz and Nieva) and Phlebotomus papatasi (Scopoli) to 10 insecticides using a modified version of the World Health Organization (WHO) exposure kit assay and Centers for Disease Control and Prevention (CDC) bottle bioassay. Sand flies were exposed to insecticides coated on the interior of 0.5-gallon and 1,000-ml glass bottles. Following exposure, the flies were allowed to recover for 24 h, after which mortality was recorded. From dose–response survival curves for L. longipalpis and P. papatasi generated with the QCal software, LCs causing 50, 90, and 95% mortality were determined for each insecticide. The LCs and LTs from this study will be useful as baseline reference points for future studies using the CDC bottle bioassays to assess insecticide susceptibility of sand fly populations in the field. There is a need for a larger repository of sand fly insecticide susceptibility data from the CDC bottle bioassays, including a range of LCs and LTs for more sand fly species with more insecticides. Such a repository would be a valuable tool for vector management.